Names of Accommodation in Sayan Tourism Village Bali: A Linguistic Landscape Analysis - Rastitiati, Ni Kade Juli; Suprastayasa, I Gusti Ngurah Agung; Susianti, Hartanti Woro (Jurnal Penelitian Pariwisata, 2023)
This research aimed at analyzing the choices of words or terms used for commercial accommodation in Sayan Tourism Village, Bali. The data were collected by taking pictures of accommodation signages using handphone camera. The data were then selected and a number of 107 pictures were appropriate to be analyzed. Firstly, they were classifiedon the bases of similarity in choice of words and languages used and quantitatively presented. Secondly, they were analyzed using qualitative approach. The results showed that there were 21 (twenty-one) variations used in signages or name plaques to refer to accommodation namely: Cottage, Kubu, Pondok, Puri, Rumah, Bungalow, Villa, Resort, House, Guesthouse, House, Accommodation, Casa, combination of Kubu and House, Kubu and Villa, Pondokand Griya, Pondokand Guest House, Pondok and Villa, Casaand Villa, Villa and Rumah, and using name only without word representing accommodation. It was also found out thatmultilingualism existed in the naming of accommodation, by using Balinese, Indonesian, English and Italian. The term “villa” wasthe most frequently used then followed by “pondok”, and “house”. The other terms were not used as many as these three terms. Keywords: choice of words, accommodation, linguistic landscape, Sayan tourism village